Work-life Balance And Subjective Well-being : The Mediating Role Of Job Satisfaction On Employees Of PT Semen Padang - Barutu, Lina Rustiana; Trinanda, Okki (Universitas Negeri Padang, 2024)
Purpose of Study: (1) Effects of Work-Life Balance on Individuals' Perceived Well-Being 2) how a healthy work-life balance affects contentment in one's position the impact of contentment in one's work on one's sense of well-being (4 ) how contentment with one's professional life influences one's subjective well-being. This study employs quantitative methods and is based on causal principles. One hundred and eighty-eight individuals who worked at PT Semen Padang made up the study's population and sample. I am collecting data using a survey that uses a Likert scale. The method used in the study was PLS (Partial Least Square), a structural equation modeling method implemented in SmartPLS 4. The study's data processing findings show that: (1) PT. Semen Padang workers' subjective well-being is positively and significantly impacted by work-life balance. T (2) PT. Semen Padang workers report higher levels of job satisfaction when they are able to strike a comfortable balance between their professional and personal lives. Personnel at PT. Semen Padang report higher levels of subjective well-being when they are satisfied with their jobs. Four, PT Semen Padang workers' subjective well-being is positively and significantly impacted by work-life balance, as measured by job satisfaction.